2007
DOI: 10.1111/j.1440-1681.2007.04747.x
|View full text |Cite
|
Sign up to set email alerts
|

CELLULAR DISTRIBUTION OF THE RENAL BUMETANIDE‐SENSITIVE Na–K–2Cl COTRANSPORTER BSC‐1 IN THE INNER STRIPE OF THE OUTER MEDULLA DURING THE DEVELOPMENT OF HYPERTENSION IN THE SPONTANEOUSLY HYPERTENSIVE RAT

Abstract: 1. The renal bumetanide-sensitive Na-K-2Cl cotransporter (BSC-1) is expressed only in the thick ascending limb and selectively traffics from intracellular vesicles (IVs) to apical plasma membranes (PMs), where BSC-1 regulates sodium reabsorption. We showed previously that in kidneys from adult spontaneously hypertensive rats (SHR; model of essential hypertension) total protein expression of BSC-1 was higher compared with kidneys from normotensive Wistar-Kyoto (WKY) rats. However, whether this change is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For instance, progression from pre-hypertensive to hypertensive state in spontaneously hypertensive rats (SHR) is accompanied by an increase in steady-state protein levels of NKCC2 and its distribution to plasma membrane compared to control rats [37,38]. Interestingly, the same amount of NKCC2 mRNA has been found in both SHR and control rats suggesting that the NKCC2 overexpression was due to a greater translational efficiency or an enhanced membrane stability of the cotransporter in SHR rats.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, progression from pre-hypertensive to hypertensive state in spontaneously hypertensive rats (SHR) is accompanied by an increase in steady-state protein levels of NKCC2 and its distribution to plasma membrane compared to control rats [37,38]. Interestingly, the same amount of NKCC2 mRNA has been found in both SHR and control rats suggesting that the NKCC2 overexpression was due to a greater translational efficiency or an enhanced membrane stability of the cotransporter in SHR rats.…”
Section: Discussionmentioning
confidence: 87%
“…This was studied by Sonalker et al [7] who showed that Na/K/2Cl co-transporter expression is higher in outer medullas of hypertensive rats [9]. These data suggest a potential role for the Ang II/ADH interaction in the TAL in this model of hypertension, implying a concomitant enhancement of the Na/K/2Cl co-transporter membrane expression.…”
Section: Discussionmentioning
confidence: 76%
“…Although the mechanism of interaction remains the same, the additive or superimposed hormonal effects are observed only in hypertension. This could be due to the fact that V2 receptors and Ang II receptors might be upregulated [5 ]or because the genetic model we used has an enhanced tendency to increase transport [7], as has been shown by other investigators in other medullar segments of the nephron.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations